The Application of Global Positioning Systems (GPS) and Linear Variable Differential Transducers (LVDT) for Bridge Deformation Monitoring - Selassie David Mayunga; M. Bakaone (Research Developments in Science and Technology Vol. 3, 2022)
Civil engineers are responsible for measuring and analyzing the deformation of engineering structures such as dams, bridges, and high-rise buildings. All civil engineering constructions are subject to deterioration over time. Bridges, in particular, deteriorate as a result of loading conditions, environmental changes, ground movement, construction materials, and steel corrosion. The most significant component of such a structure is continuous monitoring, which gives quantitative information, analyses the structure’s state, discovers risky positions, and offers early safety steps to be implemented before it threatens the safety of vehicles, goods, and human life. The standard practice for the monitoring of bridges in most developing countries has been periodical visual inspections, relying on inspectors to identify areas and signs of damages or unusual behaviors. The goal of this research is to integrate GPS and Linear Variable Differential Transducers (LVDT) to monitor bridge deformation. The vertical deflections, accelerations, and strain were measured using Linear Variable Differential Transducers, while the horizontal positions of reference and monitoring sites were established using the Global Positioning System (GPS) (LVDT). The highest displacements recorded in the x, y, and z components between zero and first epochs are 0.798m at point LT08, 0.865m at position BR13, and 0.56m at point LT02, according to the results. LVDT sensors 1, 2, and 3 had maximum deformations of 28.563mm, 31.883mm, and 40.926mm, respectively. The correlation coefficient for the observations was 0.679 with standard deviations of 0.0168 and 0.0254 in x and y respectively.